The Molecular Adaptive Responses of Skeletal Muscle to High-Intensity Exercise/Training and Hypoxia - Li, Jia (Antioxidants (Basel), 2020)
High-intensity exercise/training, especially interval exercise/training, has gained popularity in recent years. Hypoxic training was introduced to elite athletes half a century ago and has recently been adopted by the general public. In the current review, we have summarised the molecular adaptive responses of skeletal muscle to high-intensity exercise/training, focusing on mitochondrial biogenesis, angiogenesis, and muscle fibre composition. The literature suggests that (peroxisome proliferator-activated receptor gamma coactivator 1-alpha) PGC-1α, vascular endothelial growth factor (VEGF), and hypoxia-inducible factor 1-alpha (HIF1-α) might be the main mediators of skeletal muscle adaptations to high-intensity exercises in hypoxia. Exercise is known to be anti-inflammatory, while the effects of hypoxia on inflammatory signalling are more complex. The anti-inflammatory effects of a single session of exercise might result from the release of anti-inflammatory myokines and other cytokines, as well as the downregulation of Toll-like receptor signalling, while training-induced anti-inflammatory effects may be due to reductions in abdominal and visceral fat (which are main sources of pro-inflammatory cytokines). Hypoxia can lead to inflammation, and inflammation can result in tissue hypoxia. However, the hypoxic factor HIF1-α is essential for preventing excessive inflammation. Disease-induced hypoxia is related to an upregulation of inflammatory signalling, but the effects of exercise-induced hypoxia on inflammation are less conclusive. The effects of high-intensity exercise under hypoxia on skeletal muscle molecular adaptations and inflammatory signalling have not been fully explored and are worth investigating in future studies. Understanding these effects will lead to a more comprehensive scientific basis for maximising the benefits of high-intensity exercise.